Preparation and Characterization of Latex Particles as Potential Physical Shale Stabilizer in Water-Based Drilling Fluids - Junyi Liu; Zhengsong Qiu; Wei’an Huang; Dingding Song; Dan Bao (The Scientific World Journal)
The poly(styrene-methyl methacrylate) latex particles as potential physical shale stabilizer were successfully synthesized with potassium persulfate as an initiator in isopropanol-water medium. The synthesized latex particles were characterized by Fourier transform infrared spectroscopy (FT-IR), particle size distribution measurement (PSD), transmission electron microscopy (TEM), and thermal gravimetric analysis (TGA). FT-IR and TGA analysis confirmed that the latex particles were prepared by polymerization of styrene and methyl methacrylate and maintained good thermal stability. TEM and PSD analysis indicated that the spherical latex particles possessed unimodal distribution from 80 nm to 345 nm with the D90 value of 276 nm. The factors influencing particle size distribution (PSD) of latex particles were also discussed in detail. The interaction between latex particles and natural shale cores was investigated quantitatively via pore pressure transmission tests. The results indicated that the latex particles as potential physical shale stabilizer could be deformable to bridge and seal the nanopores and microfractures of shale to reduce the shale permeability and prevent pore pressure transmission. What is more, the latex particles as potential physical shale stabilizer work synergistically with chemical shale stabilizer to impart superior shale stability.